The Influence Of Brand Awareness, Consumer Trust, And Charging Infrastructure On Consumers’ Intention To Use Wuling Electric Vehicles In Medan City - Tomy; Ferry Hidayat (International Journal of Economics (IJEC), 2026)
This study aims to analyse the effect of brand awareness, consumer trust, and charging infrastructure on consumers’ intention to use Wuling electric vehicles in Medan City. The increasing development of electric vehicle technology in Indonesia has encouraged automotive companies to improve marketing strategies and infrastructure readiness in order to increase public adoption of electric vehicles. This study uses a quantitative approach with associative methods to examine the relationship between the independent variables and consumers’ intention to use electric vehicles. A total of 160 questionnaires were distributed using purposive sampling techniques. However, only 96 questionnaires were returned completely and considered valid for analysis. Data were collected through questionnaire instruments related to brand awareness, consumer trust, charging infrastructure, and intention to use variables. Data analysis was conducted using multiple linear regression techniques with the assistance of Statistical Package for Social Sciences (SPSS). The results of partial analysis showed that brand awareness has a positive and significant effect on consumers’ intention to use Wuling electric vehicles with a value of tcount = 4.259 greater than Ttable = 1.985 and significance 0.000 (<0.05). Charging infrastructure also has a positive and significant effect with a value of tcount = 8.939 greater than Ttable = 1.985 and significance 0.000 (<0.05). However, consumer trust does not significantly affect consumers’ intention to use Wuling electric vehicles because the significance value is 0.087 (>0.05). Simultaneously, all independent variables significantly affect intention to use electric vehicles with an Fcount value of 106.627 and an adjusted R square value of 76.90